Technology electroslag chill casting engineering products - Sergey Nikolaevich Zherebtsov; Yevgeny Aleksandrovich Chernyshov; Aleksander Aleksandrovich Aleksandrov; Viktor Ivanovich Gurdin (Вестник СибАДИ, 2017)
A new technology of production engineering products comprising electro slag melting the consumable electrode in the melting tank, the molten modifying ultra fine powder complexes and subsequently pouring it together with the slag in a metal mold. The comparative results of the physical and mechanical properties of products produced by various casting techniques, shows the macro- and microstructure of cast metal products "core horn-shaped" heat-resistant nickel alloy foundry.